Quality of life and lived experience of patients with short bowel syndrome treated with teduglutide and weaning off home parenteral nutrition: a qualitative analysis of patient diaries - Brian Jurewitsch; Colette Peters; Carol Okamoto (BMJ Open Gastroenterology)
Objective This study aimed to explore the lived experiences and coping strategies of patients with short bowel syndrome (SBS) prescribed teduglutide and weaning off home parenteral nutrition (HPN), and to compare the quality of life (QOL) of these patients to patients with SBS but not prescribed teduglutide.Methods A qualitative study was conducted, with patients recruited from a specialist HPN clinic. Participants completed handwritten semi-structured daily diaries for 6 weeks and a validated Home Parenteral Nutrition-Quality of Life (HPN-QOL) paper-based questionnaire as part of what aimed to be a mixed methods cross-tracks study. Participants were age-matched with patients with SBS receiving HPN but not prescribed teduglutide, and these ‘controls’ also completed the HPN-QOL questionnaire. Data analysis involved qualitative analysis of diary entries using grounded theory methodology and descriptive analysis of HPN-QOL questionnaire responses.Results Five participants completed the study and were matched with four ‘controls’. All participants and ‘controls’ reported a high QOL with no differences observed between patients prescribed and not prescribed teduglutide. Qualitative analysis revealed that participants engaged in iterative cycles of problem-focused action and emotion-focused coping strategies to manage their condition and wean off parenteral nutrition (PN). Key subthemes included polyphagia and pleomorphism in diet, fatigue-related emotional distress and positive reframing using an objective scientific lens. Decisional regret was absent, participants agreed that treatment with teduglutide was the right choice for them, despite its challenges. Their goal of independence from PN was the main motivating factor.Conclusion This study provides valuable insights into the lived experiences and coping strategies of patients with SBS prescribed teduglutide to wean off PN. The findings underscore the importance of healthcare teams understanding these everyday challenges to facilitate shared decision-making and tailor care plans. Further research is needed to explore the long-term impact of teduglutide on QOL, including the validation of tools to screen for fatigue-related emotional distress and the development of targeted interventions to support patients during the weaning process.